Evaluasi Koefisien Tanaman Padi Pada Berbagai Perlakuan Muka Air - Nur Aini Iswati Hasanah; Budi Indra Setiawan; Chusnul Arif; Slamet Widodo (Jurnal Irigasi, 2015)
Paddy is the main agricultural commodity in Indonesia that needs a large amount of water. Accurate prediction of crop water use is essential to have an efficient irrigation system. The actual evapotranspiration (ETc) is an important factor for estimating water use. Moreover, crop coefficient (Kc) is one of the important parameters in ETc calculation. In this study, Kc of paddy is estimated by using experimental pots under various water tables treatments. The water table is controlled by using mariotte tube and set at -12 cm, -7 cm, -5 cm, -3 cm, 0 cm, and +2 cm from the soil surface. From the experimental sets, the value Kc is calculated by using modified water balance equation and Kalman Filter. The result shows that water table treatment in paddy farming influences soil moisture ( ) and soil temperature (Tsoil). Soil physic parameter fluctuation due to water table treatment affects the plant growth and potential evapotranspiration. Kc value at each water table treatment is different, and varies with plant growth phase. The average Kc for all water table treatments are 0.77-1.27 (initial season), 0.90-1.11 (crop development), 1.10-1.39 (mid-season), and 1.17-1.40 (late season).